2015
DOI: 10.1177/1046878115596390
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics and Simulation/Gaming

Abstract: Purpose. This article summarizes the nine contributions to the symposium on system dynamics. The goal of the symposium is to investigate how research in system dynamics is contributing to simulation-gaming, and how the more general field of simulation-gaming is influencing work in system dynamics. Summary of articles. We summarize the nine contributions. They include five articles on basic research in learning and teaching principles for system dynamics, three articles on interactive learning environments, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…The testing of hypotheses H1 and H2 evidences that the students submitted to those transparent conditions are able to acknowledge certain cause-and-effect relations, but they fail to mentally simulate the model behaviour. This conclusion is in line with a learning difficulty frequently mentioned in systems dynamics literature (Alessi & Kopainsky, 2015; Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure. Particularly, various studies (Alessi & Kopainsky, 2015; Fischer et al, 2015; Strohhecker & Größler, 2015; Sweeney & Sterman, 2000) reported that learners tend to misunderstand stocks and flows.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The testing of hypotheses H1 and H2 evidences that the students submitted to those transparent conditions are able to acknowledge certain cause-and-effect relations, but they fail to mentally simulate the model behaviour. This conclusion is in line with a learning difficulty frequently mentioned in systems dynamics literature (Alessi & Kopainsky, 2015; Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure. Particularly, various studies (Alessi & Kopainsky, 2015; Fischer et al, 2015; Strohhecker & Größler, 2015; Sweeney & Sterman, 2000) reported that learners tend to misunderstand stocks and flows.…”
Section: Resultssupporting
confidence: 83%
“…This conclusion is in line with a learning difficulty frequently mentioned in systems dynamics literature (Alessi & Kopainsky, 2015; Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure. Particularly, various studies (Alessi & Kopainsky, 2015; Fischer et al, 2015; Strohhecker & Größler, 2015; Sweeney & Sterman, 2000) reported that learners tend to misunderstand stocks and flows. The SCC model used in this experiment involves essentially stock-flow relationships and delays related to the flows and accumulations of product inventories and orders throughout the supply chain system.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These simplistic models can be described as "cognitive illusions" which hinder the correct understanding of such dynamics. The limitations to understanding complex systems hinder in turn our capability to propose effective policy measures for the sustainability crisis [13,[15][16][17][18]. In fact, previous research has shown that not only pupils of all ages, but also their teachers hold many misconceptions and misunderstandings concerning these issues [19].…”
Section: Introductionmentioning
confidence: 99%
“…their decision-making heuristics. Specifically, this article aims to emphasize that SD models can be effectively used to support research validation (Davidsen, 2000) and to explore the role that behavioral factors (Sterman and Dogan, 2015) may play in a simulation/gaming setting (Alessi and Kopainsky, 2015;Davidsen and Spector, 2015), thereby suggesting an increased relevance for the stream of research named "BehSD".…”
Section: Introductionmentioning
confidence: 99%